Control of Cellular Gene Expression by Viral Regulatory Proteins - Panning, Barbara (My University, 1994)
Herpes simplex virus type 1 and adenovirus type 5 are nuclear DNA viruses that encode a number of regulatory polypeptides that serve to facilitate expression of the viral genome at the expense of host gene expression. These viruses depend on cellular transcriptional apparatus, and viral regulatory proteins flmction primarily to ensure that host factors engage the viral template and that viral genes are expressed in the correct spatial and temporal sequence. The results presented in this thesis demonstrate that regulatory proteins encoded by herpes simplex virus and adenovirus modulate the expression of two classes of cellular genes: the globin genes and Alu repetitive sequences. Herpes simplex virus gene products were required to stimulate the expression of human α-globin, rabbit β-globin genes and Alu elements introduced into cells as part of the herpes genome. In addition, infection with herpes simplex virus or adenovirus stimulated expression of host α-globin and Alu sequences and de novo synthesized viral gene products were required for induction of these cellular genes. Viral induction of α-globin and Alu expression are both unusual instances of activated gene expression: viral infection allows the α-globin gene to escape its erythroid~restricted transcription pattern, and the viral activation of RNA polymerase III transcription of Alu sequences is the first instance of high level class III transcription of these repetitive DNA elements in vivo. The identification of the herpes implex virus and adenovirus gene products which mediate the transcriptional activation of these host sequences has contributed to the understanding of the mechanisms which regulate expression of α-globin genes and Alu repetitive elements and also of the mechanisms by which viral regulatory proteins modulate gene expression.
Keywords: Medical Sciences; Medical Sciences